Partial topology identification of tempered fractional‐order complex networks via synchronization method. (24th May 2021) - Li, Zhiming; Ma, Weiyuan; Ma, Nuri
Abstract : This paper studies the problem of partial topology identification of tempered fractional complex networks. By tempered fractional calculus theory and pinning controlling techniques of network synchronization, we propose a strategy that can greatly reduce the expense of the partial topology identification. This method can also identify the whole topology of tempered fractional complex network. Sufficient conditions are given to guarantee partial topology identification of tempered fractional complex networks by designing suitable controllers and parameters update law. This method can also achieve synchronization between the drive network and the response network. Finally, some numerical experiments are presented to verify the validity of the method.